Analisis Pengaruh Harmonisa Terhadap Rugi-Rugi Daya (Losses) Pada Transformator di Penyulang Sedap Malam - Ariana, I Gede; Arjana, I G Dyana; Rinas, I Wayan (Majalah Ilmiah Teknologi Elektro; Vol 16 No 1 (2017): (January - April) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.1601.14, 2016)
Abstract?The aim of this study is to analyze the influence of harmonic to power losses in transformator atSedapMalam feeder by using the help of ETAP power station, so we can obtain how . much the influence of harmonic in distribution system. By measuring THDv and THDi in DT0042, DT0048 and DT0319 transformator we got THDv value of 1.1% in DT0042, 1.56% in DT 48 and 1.23% in DT0319 from maximum margin of 5.0% in THDV according to IEEE 519–1992 standard. As for THDi we got the value of 9.36% in DT0042, 12.4% in DT0048 and 14.2% in DT0319 from maximum margin of 8.0% in THDi according to IEEE 519 –1992 standard. On other side, the result by running ETAP power station we got THDi value of 1.59% in D00T42, 1.95% in DT0048 and 1.71% in DT0319. As for THDv we got running result of 12.22% in DT0042, 12.96% in DT0048 and 13.54% in DT0319. Based on the result of performed analisis of the influence of harmonic to power losses in transformator at SedapMalam feeder, we obtained that the amount of power losses was 43,2 kW before having harmonic and 45,7 kW after having harmonic. The raise of 2,5 kW was caused by occurance of harmonic in DT0042, DT0048 and DT0319 transformator from total of 44 existed transformators Keywords :Distribution, Harmonic,THDv,THDi, Power Losses.
Keywords: Distribusi, Harmonisa, THDv,THDi, Rugi Daya